A restatement of the English law of contract / Andrew Burrows - Burrows, Andrew
A comprehensive guide to the law of contract in England and Wales, this Restatement comprises a number of clear and succinct rules, supported by extensive commentary. This new edition is updated with over 30 new cases and legislation to support and expand on the area of contract law.